Maintenance rituximab in newly diagnosed mantle cell lymphoma patients: a real world analysis from the Czech lymphoma study group registry†. Issue 3 (23rd February 2019) - Obr, Aleš; Prochazka, Vit; Papajik, Tomas; Klener, Pavel; Janikova, Andrea; Salek, David; Belada, David; Pytlík, Robert; Sykorova, Alice; Mocikova, Heidi; Simkovic, Martin; Campr, Vit; et al.
Abstract: We analyzed 495 MCL patients from the Czech Lymphoma Study Group data registry. With the median follow-up of 4.4 years, 51.7% patients progressed or relapsed and 34.1% died. Five-year overall survival reached 65.3% and five-year progression free survival 44.1% of the patients. Maintenance rituximab (MR) after first line therapy improved overall and progression free survival compared to the patients under observation only (both p  < .001). Elevated beta-2-microglobulin ( p  = .003), presence of systemic symptoms ( p  = .002), ECOG >0 ( p  = .003), age ( p  = .014), and MIPI ( p  < .001) were associated with MR failure. Patients who did not achieve complete remission have had two-fold higher risk of MR failure ( p  < .001). Autologous stem cell transplant reduced the risk of MR failure by 69% ( p  < .001). The MIPI and the beta-2-microglobulin were identified as independent predictors of MR failure ( p  = .02 and p  = .03, respectively). Patients who relapsed/progressed on MR reached shorter OS calculated from the MR start compared to patients without failure (HR = 15.0; p  < .001).